Data-mining bioinformatics: suggesting Arabidopsis thaliana L-type lectin receptor kinase IX.2 (LecRK-IX.2) modulate metabolites and abiotic stress responses. (1st December 2020) - Mondal, Raju; Das, Poushali
ABSTRACT: The central role of the Arabidopsis LecRK-IX.2 gene in response to biotic stress has been well established by an array of workers. So far, the role of LecRK-IX.2 in abiotic stresses has not been investigated systematically. Here, we have first investigated a comprehensive in silico survey to explore the regulation, expression pattern in responses to a wide range of abiotic stresses. The present study reveals that the LecRK-IX.2 promoter has numerous potential cis -regulatory elements (CREs) that are regulated by different stresses. AtGenExpress data elucidate that LecRK-IX.2 gene plays a potential role in responses to cold, osmotic, drought, salt, UV-B, heat, wound, and genotoxic compound. The expression profile of the co-expressed genes suggests that Arabidopsis LecRK-IX.2 gene might have a potential role in stress responses in a tissue-specific manner. Furthermore, a probable signal transduction mechanism has been described by using protein–protein interaction (PPI) dataset. Moreover, the present data-mining investigations have suggested that LecRK-IX.2 gene modulates cellular metabolites and abiotic stress responses.